2018
DOI: 10.1007/s00245-018-9511-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control of a Thermistor Problem with Vanishing Conductivity

Abstract: An optimal control of a steady state thermistor problem is considered, where the convective boundary coefficient is taken as the control variable. A distinctive feature of this paper is that the problem is considered in arbitrary dimensions, and the electrical conductivity is allowed to vanish above a threshold temperature value. The existence of a steady state is proved, an objective functional is introduced, the existence of the optimal control is proved, and the optimality system is derived.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The thermistor was discovered by Michael Faraday in 1833, who noticed that the temperature increases when the silver sulfides resistance decreases. A lot of studies of the thermistor problem can be found in [1,9,10,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…The thermistor was discovered by Michael Faraday in 1833, who noticed that the temperature increases when the silver sulfides resistance decreases. A lot of studies of the thermistor problem can be found in [1,9,10,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling and numerical simulations were investigated in [2,13,19]. For optimal control issues, we refer the reader to [12] and the references therein. Also see [1] and its references for obstacle thermistor problems.…”
Section: Introductionmentioning
confidence: 99%